Comparative analysis of the 5'-end regions of two repressible acid phosphatase genes in Saccharomyces cerevisiae. - Thill, G P (1983)
The nucleotide sequence of 5'-noncoding and N-terminal coding regions of two coordinately regulated, repressible acid phosphatase genes from Saccharomyces cerevisiae were determined. These unlinked genes encode different, but structurally related polypeptides of molecular weights 60,000 and 56,000. The DNA sequences of their 5'-flanking regions show stretches of extensive homology upstream of, and surrounding, a "TATA" sequence and in a region in which heterogeneous 5' ends of the p60 mRNA were mapped. The predicted amino acid sequences encoded by the N-terminal regions of both genes were confirmed by determination of the amino acid sequence of the native exocellular acid phosphatase and the partial sequence of the presecretory polypeptide synthesized in a cell-free protein synthesizing system. The N-terminal region of the p60 polypeptide was shown to be characterized by a hydrophobic 17-amino acid signal polypeptide which is absent in the native exocellular protein and thought to be necessary for acid phosphatase secretion.